Doublet‐Mediated DNA Rearrangement—A Novel and Potentially Underestimated Mechanism for the Formation of Recurrent Pathogenic Deletions. Issue 3 (13th January 2017) - Jahic, Amir; Hinreiner, Sophie; Emberger, Werner; Hehr, Ute; Zuchner, Stephan; Beetz, Christian
Abstract : Doublets are small local copies of unique sequence. (A) We identified pathogenic deletions which are apparently mediated by homology (grey bars) between pre‐existing doublets. (B) Hypothetical two‐step event consisting of doublet generation and subsequent doublet‐mediated deletion. The resulting sequence would be misinterpreted as resulting from a non‐homology‐based one‐step mechanism such as non‐homologous end‐joining (grey lines). ABSTRACT: Deletions and duplications of genomic DNA contribute to evolution, phenotypic diversity, and human disease. The underlying mechanisms are incompletely understood. We identified deletions of exon 10 of the SPAST gene in two unrelated families with hereditary spastic paraplegia. We excluded a founder event, but observed that the breakpoints map to identical repeat regions. These regions likely represent an intragenic "doublet, " that is, an enigmatic class of local duplications. The fusion sequences for both deletions are compatible with recombination‐based as well as with replication‐based mechanisms. Searching the literature, we identified a partial SLC24A4 deletion that involved two copies of another doublet, and was likely formed in an analogous way. Comparing the SPAST and the SLC24A4 doublets with doublets identified previously suggested that many additional doublets have a high potential for triggering rearrangements. Considering that doublets are still being formed in the human genome, and that they likely create high local instability, we suggest that a two‐step mechanism consisting of doublet generation and subsequent doublet‐mediated deletion/duplication may underlie certain copy‐number changes for which other mechanisms are currently assumed. Further studies are necessary to delineate the significance of the thus‐far understudied doublets for the formation of copy‐number variation.